Design and fabrication of voltage and current sensor boards for the medium voltage converter - Wee, Zhi Yuan (2017)
Medium voltage power converters are required for the variable speed drives in marine propulsion. The output voltage and current of the converter need to be stable and within the required limits. To ensure this they need to be sent to the master controller as feedback. The master controller monitors this feedback signal and takes action accordingly. In this project, a voltage and current sensor interface board are designed using the Altium to interface the sensors with the EtherCAT coupler, which uses the EtherCAT communication link to give feedback to the master controller (PC). The sensor interface board is designed for 50A at the primary of the LF205-S current sensor. It correctly converts the sensed current or voltage and sends it to the master where it can be monitored. In this report, we have discussed AC/DC converters, Cascaded H-bridge multilevel inverter, several high-power electronics components like power diode, thyristor (SCR), gate turn-off thyristor (GTO) and the insulated gate bipolar transistor (IGBT) used in the power converters. It also highlights the harmonic distortion caused by switching device, several ways of modulation method to eliminate harmonic distortion such as displacement (PD) modulation and sinusoidal pulse width modulation (SPWM) with bipolar switching.